Developing improved methods for cost effective viability monitoring of Aeschynomene abyssinica and A. americana - Sartie, Alieu; Woldemariam, Yeshi; Hanson, Jean; Ndiwa, Nicholas (International Seed Testing Association, 2020)
Aeschynomene americana and A. abyssinica are forage legumes that are highly valuable as livestock feed and for soil fertility improvement. Hard-seededness is a form of physical dormancy imposed by a hard seed coat and is a common phenomenon in legume seeds. We assessed dormancy breaking treatments in relation to the time and cost of performing the assessments with the objective of developing improved methods for cost effective viability monitoring in these species. Results show that scarification of seeds with a hot wire, incubating them at 25 or 30°C, and germinating them on top of paper were the most reliable and cost-effective methods for overcoming seed dormancy for viability monitoring in Aeschynomene abyssinica and A. americana. However, the species differed in their response to the dormancy breaking treatments, with no significant differences in A. americana for all the factors except accession, suggesting that efficient dormancy breaking methods in Aeschynomere is species-specific.